CHRONIC ENDOMETRITIS OLD ISSUES NEW POSSIBILITIES - Rustamova G.R; Kudratova Z.E (Western European Studies, 2024)
Chronic endometritis is a persistent alteration of the uterine mucosa that alters receptivity and tissue regeneration; pathological abnormalities resulting in altered expression of the receptor apparatus in the uterus may be responsible for the disruption of normal endometrial function
Keywords: chronic endometritis; pregnancy; women; gynaecological